Pengaruh Ekstrak Bawang Putih (Allium sativum) pada Marinasi Daging Ayam Kampung terhadap pH, Total Bakteri, Daya Hambat, dan Awal Kebusukan - Ningrum, Zahrani Kusuma; Suryaningsih, Lilis; Gumila, Jajang (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Native chicken is a commodity that is suitable for cultivation by the Indonesian people as a cheap and easy to obtain source of animal protein. Garlic (Allium sativum L.) as a marinade that contains antibacterial compounds that are able to suppress the growth of bacteria in meat. This study aims to determine the effect and best concentration of using garlic extract (Allium sativum L.) on pH, total bacteria, bacterial inhibition, and the beginning of decay of native chicken meat. This research method uses an experimental using a Complete Random Design (RAL) with 5 treatments (P0=0%, P1=10%, P2=20%, P3=30%, P4=40%) and 4 replicas. The use of garlic extract in the marinade of native chicken meat has an effect on pH and bacterial inhibition but has no effect on total bacteria and the onset of decay. The concentration of 20% (P2) of garlic extract gave the best results in the marinade of native chicken meat because it produced a pH value of 5.60, a total number of bacteria 7.29 x 106 cfu/g, an inhibition zone in Escherichia coli of 3,625, an inhibition zone in Staphylococcus aureus 2,750, and an initial decay time of 392 minutes.